Inclusive education in Uzbekistan: current challenges and potential solutions (Acta Education, 2024)
This article is dedicated to the examination of the current state of inclusive education in Uzbekistan. The author, analyzing the changes that have occurred in this field in recent years, highlights several existing issues. By considering approaches of foreign researchers to this matter and conducting empirical research, the author provides an assessment of the problems of inclusive education from a practical perspective. Based on this, she proposes a series of measures to address the challenges of inclusive education in Uzbekistan.